2013
DOI: 10.1016/j.jor.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A short series of congenital pseudoarthrosis tibia

Abstract: We have treated 12 cases of pseudoarthrosis by correction of deformity, excision of pseudoarthrotic part and bone transport by ilizarov technique. We got excellent results in 8 cases, good in 3 cases and poor in 1 case. One poor result is because of uncontrolled infection as well as pin track infection and recurrence of deformity after removal of frame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A more recent study of 12 patients treated with a bone transport reported excellent results in eight patients, good in three and poor in one. However, no further details were given and the mean follow-up was five years [ 14 ]. Boero et al had a healing rate of 65 % in 21 patients with a mean follow-up period of two years (three bone transports, none healed) and Cho et al achieved union in 22 out of 23 patients, with a mean follow-up of 9.2 years (four bone transports) [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study of 12 patients treated with a bone transport reported excellent results in eight patients, good in three and poor in one. However, no further details were given and the mean follow-up was five years [ 14 ]. Boero et al had a healing rate of 65 % in 21 patients with a mean follow-up period of two years (three bone transports, none healed) and Cho et al achieved union in 22 out of 23 patients, with a mean follow-up of 9.2 years (four bone transports) [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary surgery for knee, ankle, foot, mal-alignment and LLD increases the frustration of surgeon and agony of patient to end up with amputation of limb [9] . Involved limb is already short, removal of pathological tissue and tapering ends of bone further increases the limb-length discrepancy [10] .…”
Section: Outcome Of Congenital Pseudoarthrosis Tibia Treated With Illmentioning
confidence: 99%
“…Its clinical presentations range from extensive complete non-union of bone to simple anterolateral tibial angulation. Classifications of radiographic findings consist of hypertrophic or atrophic pseudarthrosis and dystrophic or cystic lesions [ 1 ]. CPT is a congenital, difficult, with less occurrence bone disorder in a population including neonates.…”
Section: Introductionmentioning
confidence: 99%